EFFECT OF VILLAGE APPARATUS PERFORMANCE, INTERNAL CONTROL, INFORMATION TECHNOLOGY UTILIZATION ON VILLAGE FUND ACCOUNTABILITY AND IMPLICATIONS ON QUALITY VILLAGE FINANCIAL REPORT - Hendaris, Budi; Romli, Romli (Dinasti Publisher, 2021)
Village Fund is a new policy, so it needs good accountability. As a form of responsibility for village fund management, it is necessary to make quality financial statements. This study aims to analyze the effect of village apparatus performance, internal control, and information technology on fund management accountability and its implications for the quality of financial reports. This research used quantitative and retrieval methods using survey techniques. It was conducted using 117 respondents as officials in charge of compiling financial reports in West Bandung Regency villages. Furthermore, data analysis was performed using SEM PLS with PLS 3.0. The results showed that the village apparatus performance, internal control, and information technology use affected fund management accountability and the quality of financial reports. The research results imply that creating quality village financial statements required village apparatus performance, internal control, use of information technology, and fair accountability